Frequently asked questions in Islamic finance - Kettell, Brian (Chichester : Wiley, 2010)
In this book, industry expert Brian Kettell answers some of the most frequently asked questions from his many years experience in working and teaching in Islamic finance and banking. From knowledge of the Qu'ran and Sharia'a Law, to new and old Islamic financial concepts, Islamic terms, and Islamic financial instruments and services, this book covers all the key areas that practitioners need to Islamic finance.
Includes bibliographical references and index.
oif 09/09/14
Loan.
Keywords: Finance; Banks and banking; Islamic finance